2016
DOI: 10.1080/07347332.2016.1195901
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs and relationship challenges of head and neck cancer patients and their spouses

Abstract: In head and neck cancer (HNC), couple-based interventions may be useful for facilitating treatment completion, patient rehabilitation, and improving both partners’ quality of life (QOL). With the goal of identifying targets for future interventions, we conducted a qualitative study to understand patient and spouse unmet needs and relationship challenges during curative radiotherapy for HNC. Semi-structured interviews were conducted with 6 HNC patients (83% male) and 6 spouses (83% female) within 6 months of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(110 citation statements)
references
References 35 publications
2
108
0
Order By: Relevance
“…Study characteristics (n = 23) are reported in Table 1. Sample sizes ranged from 6 30,40 to 910 39 dyads. Four studies 37‐40 (17.4%) included patients with various cancer types, whereas 19 (82.6%) studies narrowed their sample by recruiting patients with either a specific cancer type 5,10,30‐36,41,43‐47,49,50 or in one case, a few specific types 42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics (n = 23) are reported in Table 1. Sample sizes ranged from 6 30,40 to 910 39 dyads. Four studies 37‐40 (17.4%) included patients with various cancer types, whereas 19 (82.6%) studies narrowed their sample by recruiting patients with either a specific cancer type 5,10,30‐36,41,43‐47,49,50 or in one case, a few specific types 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 37‐40 (17.4%) included patients with various cancer types, whereas 19 (82.6%) studies narrowed their sample by recruiting patients with either a specific cancer type 5,10,30‐36,41,43‐47,49,50 or in one case, a few specific types 42 . There were 12 cross‐sectional observational, 5,10,30,32,34,35,39‐42,44‐46,48 6 longitudinal, 5,31,36,39,43,49 2 mixed methods, 30,47 2 qualitative, 33,40 and 1 retrospective study 50 . Fifteen studies (65.2%) were conducted in the United States, 5,10,30,32‐34,39‐47 while 8 (34.8%) were international.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer also challenges couples' established communication patterns, roles and responsibilities [10,11]. Whereas some individuals report that cancer brought them closer together, others experience adjustment and communication challenges that fuel interpersonal conflict and can even lead to divorce [12][13][14].…”
mentioning
confidence: 99%
“…Historically a relatively neglected condition, the past decade has seen increasing research interest on head and neck patients (Patterson et al, 2015) and carers (Badr et al, 2016;Balfe et al, 2016a;Balfe et al, 2016b;Balfe et al, 2016c;Balfe et al, 2016d;Balfe et al, 2016e;Hanly et al, 2016). Areas of the head and neck experience continue to be overlooked, however.…”
Section: Introductionmentioning
confidence: 99%